Utilization of Seamless Learning as a Learning Model during Covid-19 Pandemic in Indonesia - Luluk Setyowati (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2021)
One of the effects of the 2019-20 Coronavirus pandemic is relied on education throughout the world. Education in Indonesia is also affected by the COVID-19 virus. All levels of education from elementary schools to tertiary institutions (universities) both under the Indonesian Ministry of Education and Culture and those under the Indonesian Ministry of Religion are